Vibrational Spectroscopic Studies of Tenofovir Using Density Functional Theory Method - G. R. Ramkumaar; S. Srinivasan; T. J. Bhoopathy; S. Gunasekaran (Journal of Chemistry)
A systematic vibrational spectroscopic assignment and analysis of tenofovir has been carried out by using FTIR and FT-Raman spectral data. The vibrational analysis was aided by electronic structure calculations—hybrid density functional methods (B3LYP/6-311++G(d,p), B3LYP/6-31G(d,p), and B3PW91/6-31G(d,p). Molecular equilibrium geometries, electronic energies, IR intensities, and harmonic vibrational frequencies have been computed. The assignments proposed based on the experimental IR and Raman spectra have been reviewed and complete assignment of the observed spectra have been proposed. UV-visible spectrum of the compound was also recorded and the electronic properties such as HOMO and LUMO energies and were determined by time-dependent DFT (TD-DFT) method. The geometrical, thermodynamical parameters, and absorption wavelengths were compared with the experimental data. The B3LYP/6-311++G(d,p)-, B3LYP/6-31G(d,p)-, and B3PW91/6-31G(d,p)-based NMR calculation procedure was also done. It was used to assign the 13C and 1H NMR chemical shift of tenofovir.